The relationship between medical and nursing staffing and its impact on the quality of health service / Applied Research. - جثير, سعدون حمود; ثجيل, عمر عبد (Journal of Economics and Administrative Sciences, 2017)
The research aims to find out the relationship between the medical and nursing staffing and its impact on the quality of provided health service in the Yarmouk Teaching Hospital, and to understand the nature of the relationship between doctors and nurses, it has been the adoption of cooperation and conflict Kmngaran independent knowledge of the relationship between doctors and nurses and the quality of health service as a variable certified by eating five dimensions (tangibility, reliability, safety, responsiveness, empathy). The research was adopted to collect data on the questionnaire prepared medical and nursing to the angel and adopted included Likert Quintet her, and distributed to doctors working in the Yarmouk hospital in sections main hospital, nurses, namely, (surgery, internal medicine, women's, emergency) and by (302) Form for doctors and nurses included (140) of medical staffs and (164) of the Angels nursing and analyzed data descriptive analysis using Pearson's coefficient of rank to test the correlation between variables, and analysis of simple to test the impact of the decline, and ensure search four chapters devoted the first chapter of the research methodology, tools and some of the previous studies included in the two sections, which included section The first research methodology and tools The second topic dealt with the presentation of previous studies, while the second chapter of the side Alndhara research and consists of sections of three represent the intellectual and philosophical aspect of the research variables (the nature of the medical profession and the nursing profession, cooperation and conflict between doctors and nurses and the quality of health service) has been allocated the third quarter to take up relations correlation and impact of the research variables, while representing the fourth quarter Bembgesan, includes a first section conclusions, and the second section contains recommendations and proposals in order to follow a diet that is designed to provide excellent health service, and research found to a number of conclusions was most important that the cooperation and conflict is present in all sections of the hospital, but prevail over conflict cooperation in the sections of the four to the hospital, which affects positively on the quality of the health service, while the conflict has had a negative impact on the quality of health service dimensions after reliability, empathy and responsiveness, tangibility, which has seen some decline as a result of several reasons, including conflict of ideas and personal interests between doctors the nurses and the lack of respect for the views of nurses by doctors and the existence of some overlap in some of the tasks and duties between doctors and nurses and the lack of essential medicines and medical supplies and the lack of adequate number of doctors and nurses are commensurate with the volume of work and the lack of a sufficient number of beds and lack of cleanliness of mattresses and patient rooms. Finally, the research presents a number of recommendations, the most important was the need to respond quickly to the requirements of patients, and work to achieve the doctors and nurses' needs and alleviate the pressures they face at work and boost the morale of them and the need to promote and support a culture of cooperation in the hospital between doctors, nurses, and work to identify the duties and tasks and the supply of medicines and medical supplies.